Transient expression of an immunogenic envelope attachment glycoprotein of nipah virus in Nicotiana benthamiana - Gan, Khai Swan; Tan, Chon Seng; Rofina Yasmin Othman,; Jennifer Ann Harikrishna, (Penebit Universiti Kebangsaan Malaysia, 2018)
The Nipah virus is highly virulent to swine and humans. The envelope attachment glycoprotein (G) of Nipah virus plays a key role in viral entry and induction of neutralizing antibody in mammalian hosts, thus is considered a good candidate for vaccine development. Plant transient expression systems are gaining recognition as a viable alternative for the production of vaccine antigens. In this study, we expressed the Nipah virus G protein heterologously in Nicotiana benthamiana using an agroinfiltration approach. The highest expression of recombinant G protein in N. benthamiana at RNA and protein levels was detected on day 9 post-infiltration. Western blot analysis demonstrated that the purified G protein reacted specifically with rabbit anti-Nipah Virus serum, indicating its potential for vaccine use.